KAJIAN EKOWISATA UNTUK KONSERVASI MANGROVE : STUDI KASUS DI KECAMATAN LANGSA BARAT, KOTA LANGSA, PROVINSI NANGGROE ACEH DARUSSALAM - Yulie Rahayu Fitrianingsih (Journal of Aceh Aquatic Sciences, 2017)
In recent decades, the utilization of mangrove ecosystem continues to increase, not only in terms of others uses, but also in terms of the utilization of mangrove trees, both traditional and commercial. Encroachment and conversion of mangrove land into farms, residential, industrial, and so on, as well as logging by people for various puposes, rsulting in disturbed mangrove ecosystems and natural habitats damaged. The role and function of mangroves is essential and accompained by increased use of destructive activity is accompanied by a decrease in mangrove area has been properly made efforts to improve the conservation and maintenance of the mangrove ecosystem. One of the efforts to improve the conversation and rehabilitation of mangrove ecosystems through the study of ecotourism. Several location on the East Coast of Aceh Province have been succesfully rehabilitated, for example, in the village of Kuala Langsa, District of West Langsa, Langsa. This study aims to asses the potential and feasibility of mangrove ecosystem for the development of ecotourism as a conservation of natural ecosystems and to plan management strategies in the area of mangrove ecotourism should be developed that is viewed from several aspects (mangrove vegetation, wildlife, facilities and infrastructure, stakeholder participation, institutional and legislation. The method used was a descriptive exploratory method with percentage and SWOT analysis. The results of the study indicated that the mangrove ecosystem in Kuala Langsa generally more prevalent types of Rhizophora mucronata, R. apiculata and Avicennia marina. Stakeholder participation in the mangrove rehabilitation program consisting of government, NGOs, private donors and the community. Community participation in the village of Kuala Langsa more active and has had a village rehabilitation strategy to mangrove rahabilitation efforts. Kuala Langsa produce 8 rehabilitation strategy.